First-line surgery vs first-line ART to manage infertility in women with deep endometriosis without bowel involvement: A multi-centric propensity-score matching comparison. (January 2023) - Ferrier, C.; Hini, J.D.; Gaillard, T.; Grynberg, M.; Kolanska, K.; Dabi, Y.; Nyangoh Timoh, K.; Lavoue, V.; Roman, H.; Darai, E.; Bendifallah, S.
Abstract: Objective: To compare first-line surgery with first-line assisted reproductive techniques (ART) in infertile women with deep infiltrating endometriosis (DIE) without colorectal involvement. Study design: A retrospective comparative cohort study with a propensity-score matching analysis, in four tertiary-care referral centers. The population was infertile women with DIE without colorectal involvement. The patients were managed either by first-line surgery followed by spontaneous conception attempts and/or ART, or by first-line ART. 284 patients were extracted from the databases. After matching, 92 patients were compared in each group. Clinical pregnancy rates (PR) and live-birth rates (LBR) were the primary outcomes, and cumulative pregnancy rate (CPR) and cumulative live birth rate (CLBR) were the secondary outcomes. Results: The mean number of IVF-ICSI cycles per patient was 1.4, with a significant difference between the groups: 1.6 in the first-line ART group and 1.2 in the first-line surgery group (p = 0.006). The PR was significantly higher in the first-line surgery group (72 % vs 35 %; p < 0.001). In the first-line surgery group, non-ART pregnancies occurred in 18 % (17/92) while no non-ART pregnancies was noted in the first-line ART group. The LBR was significantly higher in the first-line surgery group (61 % vs 24 %; p < 0.001). After ART, the CPR were 72 % (47/67) in the first-line surgery group, and 35 % (32/92) in the first-line ART group (p < 0.001). Conclusion: After matching, our results support that first-line surgery offer higher pregnancy and live-birth rates than first-line ART in patients with DIE without colorectal involvement.